Foreign experience of mentoring in public administration ("Journal "U". Economy. Management. Finance.", 2024)
In this article an attempt is made to evaluate foreign experience of mentoring by the example of such countries as Great Britain, USA, Sweden.
Keywords: mentoring; foreign experience; personnel; employees; mentoring program; public administration